Algorithmic Dominance and The Deconstruction of Truth: Al-Ghazali’s Epistemological Critique of The Epistemic Authority of Artificial Intelligence - Mursyidul Haq Firmansyah; Fajrul Ilmi Darussalam; Arrasikhu Fililmi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Artificial intelligence (AI) not only functions as a tool for computational work, but also plays the role of a socio-technical intermediary for epistemic authority. In this paper, the authors investigate how algorithmic systems are disrupting the standards through which we identify truth and explore al-Ghazali's views on Epistemology. Qualitative library research and conceptual-philosophical analysis have been the primary methods for this research. Among the major works studied were al-Munqidh min al-Dalal, Mishkat al-Anwar, and Kitab al-‘Ilm, besides confirmed scholarship on generative AI, algorithmic mediation, and al-Ghazali.